Fate of phosphorus fractions in an adsorptive-filter subject to intra- and inter-event runoff phenomena - Berretta, Christian; Sansalone, John (Journal of environmental management, 2012)
In-situ filtration of phosphorus (P) and particulate matter (PM) transported in runoff is increasingly implemented for urban source areas. While monitoring of filter response is commonly based on an event mean of total phosphorus (TP), this study examines the fate of specific P fractions through intra- and inter-event phenomena. This continuous filter monitoring program includes 15 wet weather loadings and the dry weather periods between these events. Aqueous P adsorption and PM-bound P (suspended, settleable and sediment) filtration phenomena are examined for runoff events from a landscaped carpark with biogenic loads in Gainesville (GNV), FL. Filter response is compared to a similar aluminum oxide Al-Ox modified media filter subject to anthropogenic loads from an urban paved source area in Baton Rouge (BTR), LA. Results for the GNV filter indicate that while intra-event settleable, sediment and dissolved P fractions are controlled by the filter, the suspended P fraction remained relatively mobile compared to the other P fractions. P adsorption is primarily influenced by intra-event flow rates, contact times, runoff volume, pH and by the inter-event chemistry of runoff stored in the filter. P effluent partitioning is dominated by the suspended PM as a consequence of effective adsorption by the filter. Inter-event phenomena generate decreasing redox with commensurate increases in alkalinity, conductivity as well as dissolved P as a consequence of re-partitioning. Dissolved P fate suggests that filters should be designed and managed to remain aerobic between wet weather events. For effective separation of suspended P and PM fractions by passive filters with low driving head, sustainability of performance, including head loss {<3 kPa}, requires upstream volumetric attenuation. ► Filtration for runoff phosphorus (P) and particulate matter (PM) control is increasing. ► Monitoring is commonly as event mean concentration (EMC) of total phosphorus (TP). ► This study monitors intra- and inter-event fate of P and PM fractions for filters. ► Dissolved P is managed with adsorptive media and inter-event drainage of filter. ► Low head loss coarse media filters require volumetric attenuation for sustainable performance.